First-Principles Study on Structural and Electronic Properties of Cubic (Pm3m) And Tetragonal (P4mm) ATiO₃ (A=Pb, Sn) / Nurakma Natasya Md Jahangir Alam ...[et al.] - Md Jahangir Alam, Nurakma Natasya; Ab Malik Marwan, Nur Aisyah; Samat, Mohd Hazrie; Mohyedin, Muhammad Zamir; Hussin, Nur Hafiz; Marwan Ali, Ab Malik; Hassan, Oskar Hasdinor; Yahya, Muhd Zu Azhan; Mohamad Taib, Mohamad Fariz (Universiti Teknologi MARA Shah Alam, 2020)
This work focuses on exploring lead-free ferroelectric materials that have a comparable unique ns2 solitary pair electrons with Pb (II), for example, Sn (II) using the first-principles study. All counts were performed dependent on ultrasoft pseudopotential of Density Functional Theory (DFT) that has been executed in the Cambridge Serial Total Energy Package (CASTEP). The convergence test for cut-off energy and k-point was performed to measure the accuracy of the calculations. It is shown that the structures have threshold energy of 350 eV and k-point of 4x4x4 with Monkhorst Pack. The structural properties for both cubic and tetragonal structures ATiO3 (Pb, Sn) have shown the comparable value of the lattice parameter that was in agreement with previous work. Generalised gradient approximation (GGA) PBE displays the most exact qualities for cross-section parameters concerning exploratory qualities for both cubic PbTiO₃ while GGA-PBEsol functional is the best functional approximation for tetragonal PTO. The electronic band structure and density of states show the presence of hybridizations between anion O 2p and cation Pb 6s/Sn 5s unique solitary pair in tetragonal PTO and SnTO stage. The calculations have shown that both cubic and tetragonal structure of ATiO3 (A=Pb, Sn) has an indirect bandgap of 1.169 eV, 1.164 eV, 1.703 eV, and 1.016 eV respectively. It is shown that tetragonal structures have a higher value of bandgap compared to cubic structures.